PERSONAL RESOURCES AS MODERATORS IN RELATIONSHIP BETWEEN LEARNING ENVIRONMENT DEMANDS AND STUDENT BURNOUT - Олефір, Валерій Олександрович; Боснюк, Валерій Федорович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
Background and Aim of Study: The main aim of this study was to learn the personal resources interaction effect (self-effiacy, self-control, optimism and resilience) with the requirements of the educational environment (study load, clarity of requirements, task adequacy) on the student’s burnout. The theoretical of the study basis was the Bakker JD-R model.Material and Methods: We conducted a structural equation modeling with latent variable interactions to study data from a cross-sectional survey of student sample (N = 303; M age = 18.38, SD = 1.53).Results: The effect of the latent variable interaction – the requirements of the educational environment×personal resources – were statistically signifiant (β = – 0.11, p <0.001). Model with interaction explained 54% of the student’s burnout variance, and the percentage increase in the explained variance as aninteraction result is 14.3%.Conclusions: It has been established that personal resources (self-effiacy, self-control, optimism and hardiness) have a systematic organization and form an integral factor at the empirical indicators level – a personal resources index, which is a buffer that mitigates student burnout caused by perceived stressors of the educational environment.